Encouraging sustainable mobility: community case study on workplace initiatives in Lahti, Finland - Villanen, Marjut; Vanhamäki, Susanna; Hämäläinen, Riitta-Maija (Frontiers in Sustainability, 2023)
The transport sector represents about 30 per cent of all carbon dioxide (CO2) emissions in developed countries. Developing sustainable transport and mobility play a central role in reducing greenhouse gas emissions. Sustainable mobility means a mind shift where transport in private cars is replaced by different modes of more sustainable mobility, such as, walking, biking, and public transport. The transformation towards more sustainable mobility plays a key role in reaching CO2 emission reduction goals. However, in addition to the environmental perspective, also social and economic aspects are interconnected in the change. In this sustainability shift, employers can encourage the employees through offering and supporting new alternatives for mobility. This article aims to study how different sustainable mobility initiatives provided by an employer are adopted by employees. This case study presents a set of pilots implemented at a workplace in Lahti, Finland in May-October 2022. The mobility forms offered for commuting were fringe benefits from employment, that is, employer-subsidized commuter tickets and employer-provided bicycle benefits. Travel during the workday was supported through introducing the use of shared electric city bikes and scooters. The research data consisted of short surveys before (n=70) and at the end of the pilots (n=66), and thematic interviews (n=8) during the implementation period. The pilots were implemented in collaboration with the employer and two local universities. Before the pilots, the main part of the employee participants was using private cars for commuting and travel during the workday. Results show that the pilots were successful in introducing more sustainable ways of mobility. However, the employer’s role in preparing, supporting, and planning the continuation of support for sustainable commuting and mobility is essential.